Catalyst component for propylene polymerization or copolymerization containing waste propylene polymerization ZN catalyst, preparation method and application thereof
By grinding the waste propylene polymerized Z-N catalyst and treating the organoaluminum compound, high-activity, high standard and high bulk density catalyst components are prepared, which solves the problem of recycling and utilization of waste catalysts and achieves efficient resource utilization and environmental protection.
Patent Information
- Application Number
- CN202311801886.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The unqualified batches generated by existing propylene polymerization Z-N catalysts during the synthesis process are difficult to recycle, resulting in waste of resources and environmental pollution, and the processing process is complex and costly.
After grinding the waste propylene polymerized Z-N catalyst, it is reacted with the organoaluminum compound to form a uniform solution, and then combined with the titanium compound and the electron donor to prepare a catalyst component with high activity, high standard, high bulk density and low fine powder content.
It realizes efficient recycling and utilization of waste catalysts, reduces production costs, reduces environmental pollution, and improves the performance and environmental benefits of catalysts.
Smart Images

Figure BDA0004629092650000081 
Figure BDA0004629092650000111 
Figure BDA0004629092650000121
Abstract
Description
Technical Field
[0001] The present invention relates to a catalyst component for polyolefin, in particular to a catalyst component for propylene polymerization or copolymerization comprising a waste propylene polymerization ZN catalyst, a preparation method and application in catalyzing propylene polymerization or copolymerization. Background Art
[0002] The global polyolefin catalyst market size is approximately RMB 8.9 billion in 2022 and is expected to reach RMB 11.2 billion in 2029, with a compound annual growth rate (CAGR) of 2.9% during 2023-2029. Catalysts are at the core of all polyolefin manufacturing processes and their role is to promote polymer chain growth. Ziegler-Natta catalysts are the most commonly used polyolefin catalysts and have been developed to the fourth generation of products. Currently, 45% of polyethylene production processes use Ziegler-Natta catalysts, and in the production of polypropylene, the use of Ziegler-Natta catalysts is as high as 95%.
[0003] However, in the process of synthesizing and manufacturing propylene polymerization ZN catalysts, batches of substandard quality will inevitably be produced, mainly including low polymerization activity of the catalyst, low polymerization bulk density, a lot of fine powder, and particle size that does not meet the requirements (too large or too small); during the screening process of the catalyst, a certain amount of oversize material will be generated due to particle agglomeration. These catalysts that do not meet the requirements need to be treated as waste harmlessly in order to meet the emission standards. The main component of the discarded ZN catalyst is magnesium chloride, and it also contains titanium, electron donors, volatile components and other components. The common treatment method is generally hydrolysis, neutralization, sedimentation, solid-liquid separation and other environmentally friendly treatments. The treatment process will generate a large amount of wastewater, waste gas, waste solids and low-value waste, which increases the operating expenses of the factory and also causes waste of resources.
[0004] If the discarded propylene polymerization ZN catalyst can be recycled and reused to prepare propylene polymerization or copolymerization catalyst, this will undoubtedly provide a new solution for the discarded propylene polymerization ZN catalyst. Summary of the invention
[0005] The object of the present invention is to provide a catalyst component for propylene polymerization or copolymerization comprising a discarded propylene polymerization ZN catalyst, wherein the catalyst component for propylene polymerization or copolymerization not only has the characteristics of high activity, high isotacticity, high bulk density and low fine powder content, but also has good environmental value and economic benefits.
[0006] Another object of the present invention is to provide a method for preparing the catalyst component.
[0007] Another object of the present invention is to provide use of the catalyst component in catalyzing propylene polymerization or copolymerization.
[0008] The waste propylene polymerization ZN catalyst selected for recovery in the present invention is mainly composed of magnesium chloride, and also contains titanium, electron donor, volatile components and the like. After reacting with at least one organic aluminum compound, a solid containing magnesium can be precipitated, and then solid components are obtained through sedimentation, filtration, washing and drying. The main component of the solid components is magnesium chloride.
[0009] In the synthesis of propylene polymerization or copolymerization catalyst components, the present invention first grinds the discarded propylene polymerization ZN catalyst, then disperses it in an inert solvent, and then reacts with an organic aluminum compound to obtain a solid component, the solid component and anhydrous MgCl2 are dissolved in the solvent to form a uniform solution, and then titanium chloride or other derivatives are added dropwise to precipitate a solid precipitate containing magnesium / titanium in the presence of a precipitation aid, and at least one electron donor is further loaded on the solid precipitate to obtain a catalyst component. The prepared catalyst component is used for propylene polymerization or copolymerization, has the characteristics of high activity, high isotacticity, high bulk density, low fine powder content, and has good environmental value and economic benefits.
[0010] In order to achieve the object of the present invention, the catalyst component for propylene polymerization or copolymerization comprising a waste propylene polymerization ZN catalyst of the present invention is obtained by comprising the following reaction steps:
[0011] 1) grinding the discarded propylene polymerization ZN catalyst under nitrogen protection;
[0012] 2) dispersing at least one ground waste propylene polymerization ZN catalyst in an inert solvent, and then reacting with at least one organoaluminum compound to precipitate a solid containing magnesium, and treating to obtain a solid component;
[0013] 3) The solid component and anhydrous MgCl2 are dissolved in a solvent to form a uniform solution, which is dissolved in the presence of a precipitation aid and then cooled, and a titanium compound is added dropwise to precipitate a solid precipitate containing magnesium / titanium. At least one electron donor is further loaded on the solid precipitate, and the catalyst component is obtained after drying.
[0014] The waste propylene polymerization ZN catalyst in step 1) refers to unqualified materials produced during the preparation of propylene polymerization ZN catalyst, and its main components include chlorine, magnesium, titanium, electron donors, organic volatiles, etc.
[0015] The waste propylene polymerization ZN catalyst needs to be ground separately, and the grinding time is 0.1 to 100 hours, preferably 1 to 75 hours, and most preferably 1 to 50 hours; the grinding temperature is 0 to 100° C., preferably 10 to 75° C., and most preferably 10 to 50° C.; the average particle size of the particles after grinding is 0.1 to 200 μm, preferably 0.1 to 30 μm, and most preferably 0.1 to 15 μm.
[0016] In step 2), the general formula of the organoaluminum compound is AlR 4 m X 3 3-m , where R 4 is hydrogen, a hydrocarbon group having 1 to 20 carbon atoms, X 3 is a halogen, and m is 0≤m≤3. The organoaluminum compound is selected from at least one alkylaluminum and alkylaluminum halide; the alkylaluminum compound is such as triethylaluminum, tributylaluminum, triisobutylaluminum, tri-n-hexylaluminum, tri-n-octylaluminum, and alkylaluminum halide is such as diethylaluminum monochloride, diethylaluminum dichloride, sesquiethylaluminum, diisobutylaluminum dichloride, diisopropylaluminum monochloride, and methyl n-propylaluminum monochloride; preferably, alkylaluminum and alkylaluminum chloride are combined in a certain proportion. Most preferably, the alkylaluminum is 0.1 to 2 moles per mole of magnesium compound in the recovered waste ZN catalyst; and the alkylaluminum halide is 0.2 to 10 moles per mole of magnesium compound.
[0017] The organic aluminum compound is added to the waste propylene polymerization ZN catalyst for sufficient chemical reaction, which can completely destroy the chemical combination between magnesium chloride, titanium compound and electron donor in the waste ZN catalyst, remove some ester compounds and titanium compounds, and form a magnesium compound carrier that can be reused.
[0018] In order to disperse evenly, an inert solvent is added, and the inert solvent can be an aromatic compound, an alkane compound or a mixture of any proportion thereof which is liquid at room temperature. The aromatic compound is: benzene, toluene, xylene, ethylbenzene, propylbenzene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc. The alkane compound includes: hexane, heptane or decane. Aromatic hydrocarbons and alkanes can be used alone or in combination, and toluene is most preferred.
[0019] In the used waste propylene polymerization ZN catalyst, magnesium chloride, titanium compound and electron donor are in a stable binding state. When recycling the propylene polymerization ZN catalyst, it is necessary to destroy the crystal structure of magnesium chloride, destroy the chemical bonding between magnesium chloride, titanium compound and electron donor, and remove the electron donor as much as possible. Therefore, in step 1), grinding is mainly used to destroy the crystal structure of magnesium chloride, and step 2) is mainly used to destroy the chemical bonding between magnesium chloride, titanium compound and electron donor, and remove the electron donor as much as possible.
[0020] For step 3), preferably, the waste propylene polymerization ZN catalyst and anhydrous magnesium chloride are mixed in any proportion; the amount is calculated based on 1 mole of the magnesium compound contained, and preferably the molar ratio of the waste propylene polymerization ZN catalyst to the anhydrous magnesium chloride is 1:0.01-100, and more preferably the molar ratio of the waste propylene polymerization ZN catalyst to the anhydrous magnesium chloride is 1:0.1-50.
[0021] In step 3), the general formula of the titanium compound is TiX 2 n (OR 3 ) 4-n , where R 3 is an aliphatic hydrocarbon group or an aromatic hydrocarbon group having 1 to 14 carbon atoms, and X 2 is a halogen, and n is 0, 1, 2, 3 or 4. Preferably, the titanium compound comprises titanium halides, alkyl titanium halides and alkoxy titanium, wherein titanium halides are such as titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, alkyl titanium halides are such as methoxy titanium trichloride, ethoxy titanium trichloride, propoxy titanium trichloride, n-butoxy titanium trichloride, dimethoxy titanium dichloride, diethoxy titanium dichloride, dipropoxy titanium dichloride, di-n-butoxy titanium dichloride, trimethoxy titanium chloride, triethoxy titanium chloride, tripropoxy titanium chloride, tri-n-butoxy titanium chloride, alkoxy titanium such as tetraethoxy titanium, tetrapropoxy titanium, tetrabutoxy titanium. These titanium compounds can be used in combination of one or more. Among them, titanium halides are preferably used. More preferably, titanium tetrachloride.
[0022] Wherein, the titanium compound is 0.05 to 50 moles, preferably 0.1 to 10 moles, and most preferably 0.1 to 5 moles, per mole of magnesium compound in the recovered waste ZN catalyst.
[0023] The solvent used to dissolve the solid component and anhydrous MgCl2 can be an organic solvent or an inert solvent. The organic solvent is an organic epoxide and / or an organic phosphorus compound. Preferably, a certain amount of organic epoxide, organic phosphorus compound and inert solvent are used for dissolution.
[0024] The organic epoxy compound is selected from compounds including oxides, glycidyl ethers and internal ethers of aliphatic olefins, dienes or halogenated aliphatic olefins or dienes having carbon atoms of 2 to 8, such as ethylene oxide, propylene oxide, butylene oxide, butadiene oxide, butadiene dioxide, epichlorohydrin, methyl glycidyl ether, diglycidyl ether, etc. Epichlorohydrin is preferred.
[0025] The organic phosphorus compound is selected from hydrocarbon esters or halogenated hydrocarbon esters of orthophosphoric acid or phosphorous acid, such as trimethyl orthophosphate, triethyl orthophosphate, tributyl orthophosphate, triphenyl orthophosphate, trimethyl phosphite, triethyl phosphite, tributyl phosphite, benzyl phosphite, etc. Tributyl phosphate is preferred.
[0026] The precipitation aid is selected from one of organic acids, organic anhydrides, organic ethers, organic ketones, or mixtures thereof, such as acetic anhydride, phthalic anhydride, succinic anhydride, maleic anhydride, pyromellitic anhydride, acetic acid, propionic acid, butyric acid, acrylic acid, methacrylic acid, acetone, methyl ethyl ketone, benzophenone, methyl ether, ethyl ether, propyl ether, butyl ether, pentyl ether, etc. Phthalic anhydride is preferred.
[0027] The inert solvent can be an aromatic hydrocarbon compound, an alkane compound or a mixture thereof in any proportion that is liquid at room temperature. The aromatic hydrocarbon compound is benzene, toluene, xylene, ethylbenzene, propylbenzene, trimethylbenzene, chlorobenzene, dichlorobenzene, etc. The alkane compound includes hexane, heptane or decane. Aromatic hydrocarbons and alkanes can be used alone or in combination, and toluene is most preferred.
[0028] The molar ratio of the total amount of the solid component and anhydrous MgCl2 to the organic epoxy compound and the organic phosphorus compound is 1:0.5-10:0.5-10, and preferably the amount of the inert solvent added is more than 10 times the total mass of the solid component and anhydrous MgCl2.
[0029] The amount of the precipitation aid added is: the mass ratio of the solid component to the total amount of anhydrous MgC12 to phthalic anhydride is 1:0.1-1, and the most preferred mass ratio is 1:0.2-0.3.
[0030] The electron donor may be a phthalate compound, which includes dimethyl phthalate, diethyl phthalate, dipropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, and di-n-octyl phthalate; di-n-butyl phthalate and diisobutyl phthalate are most preferred.
[0031] Wherein, based on each mole of magnesium compound in the recovered waste ZN catalyst, the electron donor is 0.01 to 20 moles, preferably 0.1 to 10 moles, and most preferably 0.1 to 5 moles.
[0032] Another object of the present invention is to provide a method for preparing the catalyst component, comprising the steps of:
[0033] 1) grinding the discarded propylene polymerization ZN catalyst under nitrogen protection;
[0034] 2) dispersing at least one ground waste propylene polymerization ZN catalyst in an inert solvent, and then reacting with at least one organoaluminum compound to precipitate a solid containing magnesium, and treating to obtain a solid component;
[0035] 3) The solid component and anhydrous MgCl2 are dissolved in a solvent to form a uniform solution, which is dissolved in the presence of a precipitation aid and then cooled, and a titanium compound is added dropwise to precipitate a solid precipitate containing magnesium / titanium. At least one electron donor is further loaded on the solid precipitate, and the catalyst component is obtained after drying.
[0036] The recovered waste propylene polymerization ZN catalyst, inert solvent, organic aluminum compound, titanium compound, etc. in the preparation method of the catalyst component have the same scope and structure as the above content.
[0037] The grinding time in step 1) of the catalyst component preparation method is arbitrary, preferably 1 to 50 hours; the grinding temperature is also arbitrary, preferably 10 to 50° C. The effect of grinding is to form uniform small particles of the waste recovered catalyst, most preferably 0.1 to 15 μm.
[0038] The reaction temperature in step 2) of the preparation method of the catalyst component is arbitrary, preferably 50-200° C.; in the case of selectively adding an inert solvent, it is preferably not higher than the boiling point of the selected inert solvent.
[0039] The treatment includes sedimentation, filtration, washing and drying steps.
[0040] The dispersion time is also arbitrary, as long as the ground waste recovery catalyst can be evenly dispersed.
[0041] When the organoaluminum compound is added dropwise, it can be a pure substance or a dilute solution prepared with an inert solvent. It is preferably prepared as a solution and added dropwise to reduce the reaction rate during the addition. The reaction temperature can be selected not higher than the boiling point of the inert solvent contained in the homogeneous solution and the organoaluminum compound, preferably 20 to 100°C. The time of addition is arbitrary, preferably not more than 10 hours. After the addition is completed, the reaction temperature can be appropriately increased to make the reaction more complete. The reaction temperature is preferably not more than the boiling point of the inert solvent in the system, preferably 20 to 100°C. The time of addition is arbitrary, preferably not more than 10 hours. After the addition is completed, the reaction temperature can be appropriately increased to make the reaction more complete. The reaction temperature is preferably not more than the boiling point of the inert solvent in the system, preferably 20 to 100°C. The processes of sedimentation, filtration, washing, etc. can be selectively repeated multiple times to remove free chemical substances. The temperature of the above operation is arbitrary, preferably not more than the boiling point of the inert solvent used. The time of the above operation is arbitrary. The solid component finally separated is vacuum dried or dried with nitrogen to obtain a solid component.
[0042] In the preparation method of the catalyst component, in step 3), a solid component and anhydrous MgCl2 are added to a reactor in any proportion, and then dissolved with a certain amount of solvent, the dissolution temperature is preferably 20 to 60°C, and then the titanium compound is added dropwise to a certain temperature, preferably -10°C to -40°C. Then the temperature is slowly raised to precipitate the solid, an electron donor of a phthalate compound is added, and then the solid is treated with a mixed solution of toluene and titanium tetrachloride, and then fully washed with an inert solvent (such as toluene and hexane) and vacuum dried to obtain the catalyst component.
[0043] The catalyst component of the present invention and an organic aluminum compound can form a catalyst for propylene polymerization or copolymerization.
[0044] The organoaluminum compound has been widely recognized and applied as a component of olefin catalyst. Its general formula is AlR 5 y X 4 3-y , where R 5 is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X 4 is halogen, and y is 1, 2 or 3.
[0045] The organoaluminum compound includes trialkylaluminum compounds, alkylaluminum halides and mixtures thereof in any proportion, preferably triethylaluminum, triisobutylaluminum, diethylaluminum monochloride, ethylaluminum dichloride, and more preferably triethylaluminum and triisobutylaluminum.
[0046] The catalyst system of the present invention is used for propylene polymerization or copolymerization, and the copolymerization monomer can be propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-pentene, etc. The catalyst system of the present invention is suitable for slurry polymerization, bulk polymerization and gas phase polymerization. It is particularly suitable for homopolymerization of propylene, random copolymerization of propylene and ethylene, and multiphase impact copolymerization.
[0047] The inventors have found through repeated experiments that under nitrogen protection, with waste ZN catalyst as raw material, the particle size can be controlled by grinding at a certain temperature, the magnesium chloride crystals in the waste ZN catalyst after grinding are randomly and disorderly arranged, and the physical structure of the waste ZN catalyst is completely destroyed; an organic aluminum compound (alkyl aluminum halide or alkyl aluminum) is added to carry out a sufficient chemical reaction, and the titanium compound is Ti 4+ Reduction to Ti 3+ and Ti 2+At the same time, the organoaluminum compound (alkyl aluminum halide or alkyl aluminum) plays the role of a halogenating agent, reacts with the alkoxy group in the solution, completely destroys the chemical combination between magnesium chloride, titanium compound and electron donor, and forms new magnesium chloride as a carrier; the organoaluminum compound (alkyl aluminum halide or alkyl aluminum) undergoes a reduction reaction with the electron donor in the discarded ZN catalyst, first reducing dibutyl phthalate to butanol and phthalic acid methanol, and then continuing to react with the organoaluminum compound (alkyl aluminum halide or alkyl aluminum) to generate aluminum compounds, which are washed with saturated alkanes for many times and finally remove the electron donor compound. After the treated solid component and anhydrous MgCl2 are dissolved in a solvent, the titanium compound is added dropwise, and the internal electron donor is added to obtain a catalyst component. The catalyst component finally obtained can be used for propylene polymerization or copolymerization, and not only has the characteristics of high activity, high isotacticity, high bulk density, and low fine powder content, but also has good environmental value and economic benefits.
[0048] The invention provides a catalyst component for propylene polymerization or copolymerization recovered from waste polypropylene ZN catalyst as raw material, a preparation method and application thereof. The catalyst component for propylene polymerization not only has the characteristics of high activity, high isotacticity, high bulk density, uniform particle size distribution and low fine powder content, but also has good environmental value and economic benefits. DETAILED DESCRIPTION
[0049] The present invention is further described below with examples, which is conducive to a better understanding of the present invention and its advantages and effects, but the examples are only used to illustrate the present invention rather than to limit the present invention.
[0050] Characterization
[0051] Composition of the catalyst The metal elements in the catalyst were determined by spectrophotometry, the halogen was determined by silver nitrate titration, and the alkoxy was determined by gas chromatography.
[0052] Particle size distribution of polymer
[0053] ASTM E1187
[0054] Melt index measurement
[0055] ASTM D1238
[0056] Bulk density of polymer
[0057] DIN 53194
[0058] The contents of components ① to ④ and particle size distribution of the recovered waste ZN catalyst are shown in Table 1.
[0059] Table 1 Component content and particle size of recycled waste ZN catalyst
[0060]
[0061] Example 1
[0062] 1. Preparation of catalyst components:
[0063] Take 20g of the recycled waste ZN catalyst ① and grind it in a grinding kettle under nitrogen protection for 12h. The temperature in the grinding kettle is 30℃. After grinding, the mixture is protected by nitrogen in a closed container. The particle size after grinding is tested to be 12.8μm. Dissolve the ground waste catalyst in 300ml of toluene. After sufficient dissolution, add 100ml of 5mol / L diethylaluminum monochloride toluene solution within 2h, stir for 30min, then add 10ml of 5mol / L trihexylaluminum toluene solution, stir for 60min, and heat it to 90℃ at a uniform speed. Solids gradually precipitate during the heating process. After filtering, wash it 4 times with 500ml of hexane, and vacuum dry it to obtain the solid component.
[0064] In a 500ml 5-necked flask with nitrogen fully replaced and stirred, add 5g of treated solid component and 5g of anhydrous magnesium chloride, 150ml of toluene, 17ml of epichlorohydrin and 16ml of tributyl phosphate, stir and heat to 50°C, and maintain for 2 hours. The solid is completely dissolved, then add 2.4g of phthalic anhydride and maintain for another hour. The solution is cooled to -25°C, 110ml of titanium tetrachloride is added dropwise within 1 hour, and the temperature is slowly raised to 80°C. During the heating process, solids are gradually precipitated. 3g of di-n-butyl phthalate is added and maintained at 80°C for 1 hour. After filtering, wash twice with 200ml of toluene, then add 12ml of toluene and 80ml of titanium tetrachloride, continue to heat to 110°C, keep constant temperature for 2 hours, then filter the liquid clean, repeat the treatment once, wash 4 times with hexane, and obtain a solid catalyst component after drying. The catalyst composition is shown in Table 2.
[0065] 2. Aggregation
[0066] After the 5L stainless steel reactor was fully replaced with nitrogen, 5mL of 0.5mol / L triethylaluminum hexane solution and 1mL of 0.1mol / L methylcyclohexyldimethoxysilane (CMMS) hexane solution and 10mg of the prepared catalyst were added, and then 10mL of hexane was added to flush the feed line, and then 2L (under standard conditions) of hydrogen and 2.5L of refined propylene were added. The reaction was controlled to prepolymerize at 20°C for 5 minutes, and the temperature was raised to 70°C. The polymerization reaction was carried out at this temperature for 1 hour. After the reaction was completed, the reactor was cooled and the stirring was stopped to discharge the reaction product, and the polymer was obtained by drying. The polymerization results are shown in Table 3.
[0067] Example 2
[0068] 1. Preparation of catalyst components: Same as Example 1, except that the grinding time was changed to 32 hours. The particle size after grinding was tested to be 9.5 μm. The catalyst composition is shown in Table 2.
[0069] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0070] Example 3
[0071] 1. Preparation of catalyst components: Same as Example 1, except that the grinding time was changed to 48 h. The particle size after grinding was tested to be 6.8 μm. The catalyst composition is shown in Table 2.
[0072] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0073] Example 4
[0074] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recovered by the waste ZN catalyst ②. The catalyst composition is shown in Table 2.
[0075] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0076] Example 5
[0077] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recycled instead of the waste ZN catalyst ③. The catalyst composition is shown in Table 2.
[0078] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0079] Example 6
[0080] 1. Preparation of catalyst components: Same as Example 1, except that the waste ZN catalyst ① is recycled instead of the waste ZN catalyst ④. The catalyst composition is shown in Table 2.
[0081] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0082] Example 7
[0083] 1. Preparation of catalyst components: Same as Example 1, except that the recovery of waste ZN catalyst ① is changed to 50% recovery of waste ZN catalyst ① and 50% recovery of waste ZN catalyst ②. The catalyst composition is shown in Table 2.
[0084] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0085] Example 8
[0086] 1. Preparation of catalyst component: Same as Example 1, except that 5g of treated solid component and 5g of anhydrous magnesium chloride are replaced by 9g of treated solid component and 1g of anhydrous magnesium chloride. The catalyst composition is shown in Table 2.
[0087] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0088] Example 9
[0089] 1. Preparation of catalyst components: Same as Example 8, except that the recovery of waste ZN catalyst ① is changed to the recovery of waste ZN catalyst ②.
[0090] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0091] Example 10
[0092] 1. Preparation of catalyst components: Same as in Example 1, except that 100 ml of 5 mol / L diethylaluminum chloride toluene solution and 10 ml of 5 mol / L trihexylaluminum toluene solution were replaced by 60 ml of 5 mol / L diethylaluminum chloride toluene solution and 50 ml of 5 mol / L trihexylaluminum toluene solution. The catalyst composition is shown in Table 2.
[0093] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0094] Comparative Example 1
[0095] 1. Preparation of catalyst components:
[0096] In a 500ml 5-necked flask with nitrogen fully replaced and stirred, add 10g anhydrous MgCl2, 150ml toluene, 17ml epichlorohydrin and 16ml tributyl phosphate, stir and heat to 50°C, and maintain for 2 hours. The solid is completely dissolved, then add 2.4g phthalic anhydride and maintain for another hour. The solution is cooled to -25°C, 110ml titanium tetrachloride is added dropwise within 1 hour, and the temperature is slowly raised to 80°C. During the heating process, solids are gradually precipitated. 3g di-n-butyl phthalate is added and maintained at 80°C for 1 hour. After filtering, wash twice with 200ml toluene, then add 12ml toluene and 80ml titanium tetrachloride, continue to heat to 110°C, keep constant temperature for 2 hours, then filter the liquid clean, repeat the process once, wash with hexane 4 times, and obtain a solid catalyst component after drying. The catalyst composition is shown in Table 2. The polymerization method is the same as in Example 1, and the polymerization results are shown in Table 3.
[0097] Comparative Example 2
[0098] 1. Preparation of catalyst components: Recover discarded ZN catalyst④ without grinding.
[0099] 2. Polymerization: Same as Example 1. The polymerization results are shown in Table 3.
[0100] Table 2 Catalyst composition and particle size distribution
[0101]
[0102] It can be seen from Table 2 and Table 3 that the solid catalyst component prepared by the present invention has the characteristics of high activity, high bulk density, uniform particle size distribution and low fine powder content. Compared with Comparative Example 1, the activity of the embodiment can reach more than 90% of the activity of Comparative Example 1. It can be seen that the treatment method in the present invention can better utilize the recyclable components in the waste catalyst and greatly reduce the cost and pollutants generated by treating the waste catalyst.
[0103] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
[0104] The terms used herein are only for illustration of specific embodiments and are not intended to limit the present invention. Unless otherwise defined, all terms (including technical terms and scientific terms) used herein are the same as those understood by those of ordinary skill in the art to which the present invention belongs. It should also be made clear that, except for clear definitions herein, terms such as those generally defined in dictionaries should be interpreted as having a consistent meaning in the context of this specification and the related art, and should not be interpreted as idealized or overly formalized.
[0105]
Claims
1. A catalyst component for propylene polymerization or copolymerization comprising a waste propylene polymerization ZN catalyst, characterized in that: It is obtained by comprising the following reaction steps: 1) grinding the discarded propylene polymerization ZN catalyst under nitrogen protection; 2) dispersing at least one ground waste propylene polymerization ZN catalyst in an inert solvent, and then reacting with at least one organoaluminum compound to precipitate a solid containing magnesium, and treating to obtain a solid component; 3) The solid component and anhydrous MgCl2 are dissolved in a solvent to form a uniform solution, which is dissolved in the presence of a precipitation aid and then cooled, and a titanium compound is added dropwise to precipitate a solid precipitate containing magnesium / titanium. At least one electron donor is further loaded on the solid precipitate, and the catalyst component is obtained after drying.
2. The catalyst component according to claim 1, characterized in that The grinding time in step 1) is 0.1 to 100 h, preferably 1 to 75 h, and most preferably 1 to 50 h; the grinding temperature is 0 to 100 ° C, preferably 10 to 75 ° C, and most preferably 10 to 50 ° C; the average particle size of the particles after grinding is 0.1 to 200 μm, preferably 0.1 to 30 μm, and most preferably 0.1 to 15 μm.
3. The catalyst component according to claim 1, characterized in that The amount of each reactant used is based on the amount of the magnesium compound in the recovered waste ZN catalyst, and the amount of the organoaluminum compound is 0.2 to 100 moles, preferably 0.2 to 20 moles, and most preferably 0.2 to 10 moles.
4. The catalyst component according to any one of claims 1 to 3, characterized in that: The general formula of the organoaluminum compound is AlR 2 m X 2 3-m , where R 2 is hydrogen, a hydrocarbon group having 1 to 20 carbon atoms; X 2 is a halogen, and m is 0≤m≤3.
5. The catalyst component according to claim 1, characterized in that The waste propylene polymerization ZN catalyst and anhydrous magnesium chloride are mixed in any proportion; calculated based on the molar amount of the magnesium compound contained in the substance, the molar ratio of the waste ZN catalyst to the anhydrous magnesium chloride is preferably 1:0.01-100, and the molar ratio of the waste ZN catalyst to the anhydrous magnesium chloride is more preferably 1:0.1-50.
6. The catalyst component according to claim 1, characterized in that The general formula of the titanium compound is TiX 1 n (OR 1 ) 4-n , where R 1 is an aliphatic group or an aromatic hydrocarbon group having 1 to 14 carbon atoms, X 1 is halogen, and n is 0, 1, 2, 3, or 4.
7. The catalyst component according to claim 7, characterized in that The titanium compound includes titanium halides, alkoxy titanium halides and alkoxy titanium, wherein titanium halides are such as titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, alkoxy titanium halides are such as methoxy titanium trichloride, ethoxy titanium trichloride, propoxy titanium trichloride, n-butoxy titanium trichloride, dimethoxy titanium dichloride, diethoxy titanium dichloride, dipropoxy titanium dichloride, di-n-butoxy titanium dichloride, trimethoxy titanium chloride, triethoxy titanium chloride, tripropoxy titanium chloride, tripropoxy titanium chloride or tri-n-butoxy titanium chloride, alkoxy titanium is such as tetraethoxy titanium, tetrapropoxy titanium, tetrabutoxy titanium; preferably titanium halides are used; more preferably titanium tetrachloride.
8. The catalyst component according to claim 1, characterized in that The electron donor is a phthalate compound, which includes dimethyl phthalate, diethyl phthalate, dipropyl phthalate, di-n-butyl phthalate, diisobutyl phthalate, and di-n-octyl phthalate; di-n-butyl phthalate and diisobutyl phthalate are most preferred.
9. The method for preparing the catalyst component according to any one of claims 1 to 8, characterized in that: It includes the following steps: 1) grinding the discarded propylene polymerization ZN catalyst under nitrogen protection; 2) dispersing at least one ground waste propylene polymerization ZN catalyst in an inert solvent, and then reacting with at least one organoaluminum compound to precipitate a solid containing magnesium, and treating to obtain a solid component; 3) The solid component and anhydrous MgCl2 are dissolved in a solvent to form a uniform solution, which is dissolved in the presence of a precipitation aid and then cooled, and a titanium compound is added dropwise to precipitate a solid precipitate containing magnesium / titanium. At least one electron donor is further loaded on the solid precipitate, and the catalyst component is obtained after drying.
10. A catalyst for olefin polymerization, characterized in that: Comprising the following components or the reaction products of the following components: a) the catalyst component according to any one of claims 1 to 9; b) and a general formula of AlR 3 y X 3 3-y An organoaluminum compound, wherein R 3 is hydrogen or a hydrocarbon group having 1 to 20 carbon atoms, X 3 is halogen, and y is 1, 2 or 3.